1999
DOI: 10.3354/ame019189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two polychaete worms, Nereis diversicolor and Arenicola marina, on aerobic and anaerobic decomposition in a sandy marine sediment

Abstract: The effects of 2 polychaete species, Nereis diversicolor and Arenicola marina, on benthic metabolism and decomposition processes in organic-poor (0.06% POC), sandy sediment were experimentally investigated. Sedvnent O2 uptake and CO2 release were stimulated by 80 to 90% and 260 to 270% for N. diversicolor and A. marina, respect~vely, from basal rates of approximately 30 mm01 m-2 d-'. These enhancements in benthic f l u e s were due to both increased solute exchange due to macrofauna irngation and increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
144
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 31 publications
(53 reference statements)
19
144
2
1
Order By: Relevance
“…In sediment core incubations, where hydrodynamic forcing was minimal, areal sedimentary OCR were slightly higher at the lugworm exclusion site. This was an anticipated result, since the generally more reduced and organic-enriched character of the sediment at the exclusion site is likely to increase diffusive oxygen consumption due to the reoxidation of accumulated reduced compounds and increased organic mineralization (Banta et al 1999;Papaspyrou et al 2007). Considering the low oxygen penetration measured in situ at the exclusion site, sedimentary oxygen consumption occurs in a relatively thin active sediment layer.…”
Section: Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sediment core incubations, where hydrodynamic forcing was minimal, areal sedimentary OCR were slightly higher at the lugworm exclusion site. This was an anticipated result, since the generally more reduced and organic-enriched character of the sediment at the exclusion site is likely to increase diffusive oxygen consumption due to the reoxidation of accumulated reduced compounds and increased organic mineralization (Banta et al 1999;Papaspyrou et al 2007). Considering the low oxygen penetration measured in situ at the exclusion site, sedimentary oxygen consumption occurs in a relatively thin active sediment layer.…”
Section: Exclusionmentioning
confidence: 99%
“…It can be speculated that dense populations of bioturbating macroinvertebrates can significantly extend the open exchange regions by their own bioirrigation, by maintaining the sediment permeability, and by creating a pit-and-mound topography of the sediment surface. Manipulated laboratory microcosms are a commonly used approach for the study of the effects of macrofauna on benthic metabolism and sediment-water exchange (e.g., Banta et al 1999), but the exclusion of physical forces has been shown to affect the magnitude of macrofaunal effects (Papaspyrou et al 2007). In situ experimental works remain few (Huettel 1990;D'Andrea et al 2002), presumably due to difficulties in manipulating species composition and measuring oxygen fluxes in an open and fluid system (Biles et al 2002).…”
mentioning
confidence: 99%
“…These mechanistic differences mean that in cohesive sediments the remineralisation of organic carbon and generation of macronutrients is largely driven by the reduction of solutes, such as nitrate and sulphate, whilst in non-cohesive sediments remineralisation processes reflect the extent of advective porewater flows (Rocha 2008). However, sediment or habitat type can be a poor predictor of biogeochemical performance (Dernie et al 2003) because the active redistribution of particles and fluids by infaunal macro-invertebrates disproportionately influences benthic fluxes and total benthic metabolism (Banta et al 1999;Mermillod-Blondin et al 2004). Hence, the level of biogeochemical performance that is realised will depend, at least in part, on the structure and composition of the post-disturbance surviving community (Solan et al 2004a;Thomsen et al 2017;Wohlgemuth et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The burrowing, ventilation and foraging activity of benthic macrofauna organisms affects key ecosystem processes of marine sediments, including organic matter remineralization, nutrient cycling, biogeochemical interactions and benthic-pelagic fluxes (Rhoads, 1974;Aller, 1982Aller, , 1988Aller, , 1994Kristensen et al, 1991Kristensen et al, , 2000Gilbert et al, 1998Gilbert et al, , 2003Banta et al, 1999). Microbial abundances and activities have been shown to increase due to the complex biogeochemical interactions induced by bioturbation activity (Hansen and Kristensen, 1998;Lohrer et al, 2004;Kogure and Wada, 2005).…”
Section: Introductionmentioning
confidence: 99%